Evaluasi pengakuan pendapatan berdasarkan PSAK No. 72 pada meter pascabayar di PT. PLN (Persero) ULP Manado Selatan - Rianto, Tribrata Putra; Manossoh, Hendrik; Korompis, Claudia W.M (Yayasan Widyantara Nawasena Raharja, 2024)
Revenue is an indicator for profit formation, therefore revenue is measured fairly in accordance with the revenue recognition principle to be applied to measure the actual income received by the company. If an income is recognized that is not the same as it should be, then this means that the income could be wrong (too big or too small). This can result in the information presented in the income statement being inaccurate. This research aims to determine revenue recognition at PT. PLN (Persero) ULP South Manado. Income from the sale of electrical energy through postpaid meters is one source of income for PT. PLN (Persero) ULP South Manado. The method used in this research is a qualitative descriptive method which aims to describe the data that has been collected as it is obtained from the results of interviews and data collected from the company. The research results show that revenue recognition at PT. PLN (Persero) ULP South Manado is in consistent with PSAK 72.